Hubungan Kepribadian Introvert terhadap Kemampuan Public Speaking - Sri Wahyu Wardani; Rovina Sellanie; Septiana Mulyani (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
This study aims to determine the relationship between introvert personality and public speaking skills of grade 3 students of SDN Lawangan Daya 2 Pamekasan. Public speaking is an important skill that supports students' self-confidence and social development, but is often a challenge for students with introvert personalities. This study uses a qualitative approach with a descriptive type. Data were collected through in-depth interviews with teachers, principals, and students, as well as through participant observation and documentation of learning activities. The results of the study indicate that introvert students tend to have difficulty in public speaking, but have advantages in compiling more in-depth and systematic materials. Environmental factors, such as interactive teaching strategies and teacher support, play an important role in reducing speaking barriers experienced by introvert students. With the right learning approach, introvert students are able to develop their speaking skills optimally. This study recommends the importance of adaptive teaching strategies to support the potential of introvert students in public speaking.